A Sustainable Way to Generate Energy through Biomass Flash Pyrolysis in South Asia: A Green Energy Technology - Enam, Rabia Noor; Tahir, Muhammad; Rizvi, Huma Hasan; Rafique, Asim; Mustafa, Syed Muhammad Nabeel (International Journal of Energy Economics and Policy, 2022)
Asian Countries mostly lying in Subcontinent region are the main producers of Sugar canes. On the other hand, these are the developing countries which mostly face potential energy crisis which ultimately gives rise to sustainable electricity demand challenges. This challenge can be mitigated through the conventional way of bagasse-based cogeneration of power. Therefore, sugar industries can contribute in fulfilling at least their own requirement of plant electricity. But this method in turn produces carbon dioxide (CO2) to the environment which is a major source of Green House Gas (GHG) emissions globally. So, it is the most significant contributor to the global warming, which plays diverse impact on social, environmental, and economic costs. So far, the increasing concentrations of GHGs in the atmosphere are a notable issue. Biochar is one of the products of flash pyrolysis which reduces the GHG emissions and enhancement of soil fertility. This paper proposes flash pyrolysis as a sustainable way of meeting electricity demand with additional benefits over conventional way of burning bagasse in cogeneration, giving the environmental and economic benefits of pyrolysis. Bagasse gasification by flash pyrolysis in the sugar mills could be an alternative option for electricity generation with CO2 negative impact.